(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the effect of different pruning heights on the agronomic characteristics of two cassava varieties. The varieties known regionally as “Amarelinha” and “Paulo Velho” were used. A randomized block design was adopted, with 12 treatments and three replications. The treatments were arranged in a 2 x 6 factorial scheme, with two cassava varieties (Amarelinha and Paulo Velho), five pruning heights (0.05 m; 0.25 m; 0.5 m; 0.75 m; 0.95 m) and witness (without pruning). The variables analyzed were: plant height, number of leaves, stem diameter, shoot dry matter content, shoot dry matter yield, total root number, commercial root number, root dry matter content, yield total root yield, commercial root yield, and harvest index. The data were submitted to the F test and the comparison of means by the Tukey test at 5% of significance, using the Sisvar program. According to the data obtained by analysis of variance, a significant interaction was observed for all variables except for shoot dry matter content and harvest index. The pruning height at 0.5 m high provided a positive effect on the productivity of roots and leaves, the cassava variety “Amarelinha” is the most suitable for the production of forage and roots and the variety “Paulo Velho” is indicated for the production of roots.